2006
DOI: 10.1007/s00268-005-0304-6
|View full text |Cite
|
Sign up to set email alerts
|

Appendectomy versus Antibiotic Treatment in Acute Appendicitis. A Prospective Multicenter Randomized Controlled Trial

Abstract: Acute non-perforated appendicitis can be treated successfully with antibiotics. However, there is a risk of recurrence in cases of acute appendicitis, and this risk should be compared with the risk of complications after appendectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
435
4
25

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 471 publications
(492 citation statements)
references
References 17 publications
16
435
4
25
Order By: Relevance
“…Five prospective RCTs [27][28][29][30][31] with a total of 1430 patients met the selection criteria and were eligible for inclusion. The number of patients, per protocol, allocated to the antibiotic group was 644, while 786 patients comprised the surgery group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five prospective RCTs [27][28][29][30][31] with a total of 1430 patients met the selection criteria and were eligible for inclusion. The number of patients, per protocol, allocated to the antibiotic group was 644, while 786 patients comprised the surgery group.…”
Section: Resultsmentioning
confidence: 99%
“…The most recent RCTs used ertapenem, following the previously published guidelines by the surgical infection society and the infectious diseases society of America for the management of intra-abdominal infection [34]. As for post-discharge antibiotics, four of the five selected studies used a combination of a second or third generation fluoroquinolone; ofloxacin, ciprofloxacin or levofloxacin, and a nitroimidazole; metronidazole or tinidazole [27][28][29]31]. Vons et al continued to use amoxicillin and clavulinic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Disseminated intra-abdominal infection from appendicitis, however, is not seen as often today as in the first decades of the 20th century, when appendicitis was the major cause of severe peritonitis and peritonitis-related mortality (36,37,38). Although antibiotics may be used as primary treatment for selected patients with suspected uncomplicated appendicitis, appendectomy is still the gold standard therapy for acute appendicitis (36,37,38). Treatment includes source control by appendectomy, rarely in the most severe cases staged abdominal repair in cases when peritoneal edema has led to abdominal compartment syndrome.…”
Section: Source Control Of Appendix Perforationmentioning
confidence: 99%
“…Treatment includes source control by appendectomy, rarely in the most severe cases staged abdominal repair in cases when peritoneal edema has led to abdominal compartment syndrome. Studies have demonstrated that antibiotics alone may be useful to treat patients with early, non perforated appendicitis, even if there is a risk of recurrence (36,37,38). Randomized clinical trial by Hanson et al compared antibiotic therapy versus appendectomy as primary treatment of acute appendicitis (39).…”
Section: Source Control Of Appendix Perforationmentioning
confidence: 99%
“…2,3,[4][5][6] This is review of 283 cases of acute appendicitis undergoing appendicectomy from January 2016 to December 2016 to verify whether acute non-perforated appendicitis requires immediate surgery or can be delayed being taken up on elective basis.…”
mentioning
confidence: 99%